MAP9/MAPH-9 supports axonemal microtubule doublets and modulates motor movement - Tran, Michael V; Khuntsariya, Daria; Fetter, Richard D; Ferguson, James W; Wang, Jennifer T; Long, Alexandra F; Cote, Lauren E; Wellard, Stephen R; Vázquez-Martínez, Nabor; Sallee, Maria D; Genova, Mariya; Magiera, Maria M; et al. (Developmental cell, 2024)
Microtubule doublets (MTDs) comprise an incomplete microtubule (B-tubule) attached to the side of a complete cylindrical microtubule. These compound microtubules are conserved in cilia across the tree of life; however, the mechanisms by which MTDs form and are maintained in vivo remain poorly understood. Here, we identify microtubule-associated protein 9 (MAP9) as an MTD-associated protein. We demonstrate that C. elegans MAPH-9, a MAP9 homolog, is present during MTD assembly and localizes exclusively to MTDs, a preference that is in part mediated by tubulin polyglutamylation. We find that loss of MAPH-9 causes ultrastructural MTD defects, including shortened and/or squashed B-tubules with reduced numbers of protofilaments, dysregulated axonemal motor velocity, and perturbed cilia function. Because we find that the mammalian ortholog MAP9 localizes to axonemes in cultured mammalian cells and mouse tissues, we propose that MAP9/MAPH-9 plays a conserved role in regulating ciliary motors and supporting the structure of axonemal MTDs.
Keywords: axoneme; Caenorhabditis elegans; C. elegans; kinesin; Mammals; microtubule; pohyb; axonema; Microtubules; cilia; dynein; microtubule-associated protein; cilie; savci; Animals; polyglutamylation; zvířata; mikrotubuly; Movement; MAP9; myši; Cilia; Axoneme; tubulin; Mice; microtubule doublet; Tubulin